HLA-B27 subtypes in patients with spondylarthropathies, IgE levels against some allergens and their relationship to the disease parameters - Kamanli, Ayhan; Ardicoglu, Ozge; Godekmerdan, Ahmet (Comenius Univ, 2009)
In suitable genetic backgrounds, some exogenous and/or endogenous antigens may cause SpA. In this study, we investigated HLA B27 subtypes and its relationship to some allergens and clinical findings in a group of SpA patients. Forty-eight patients (19F, 29M) with SpA (27 with ankylosing spondylitis, 5 with reactive arthritis, 15 undifferentiated and 1 with psoriatic arthritis) were included to the study. HLA-B alleles have been assessed using the LiPA (Line Probe Assay) reverse hybridization principle method. The allergens studied were following: egg white, yolk, wheat flour, hot pepper, tomatoes, olive, onion, chicken, black tea, sheep cheese, penicillin panel (m1, m25, m28, m30), fungus panel (m1, m2, m3, m6), and housemix panel (e1, e2, ell, d2, m2, m3). 59.3 % of the patients were positive for HLA-B27. Of these patients, 53.6 % had B*2702 allele which was the most common, followed by B*2708 (21.1 %) and B*2701 (10.5 %). HLA-B27 was positive in 70 % of the ankylosing spondylitis patients and 52 % had B*2702 subgroup and B35 was the most common subgroup among the patients who were HLA-B27 negative. Allergic reactions against these 13 allergens were more severe in patients HLA-B27 positive. The most frequent allergic reactions were against the onion and housemix panel, followed by red pepper, tomatoes, sheep cheese and olive. HLA-B*2702 and HLA-B*2701 subgroups had more severe allergic reactions that correlated with a disease severity (p<0.001). These results indicate that B*2702 and B*2708 is more frequent in our region in contrast to B*2705 which is more commonly found all around the world and that our region represents a heterogeneous distribution. IgE levels against some allergen were found higher in patients with SpA (Fig. 2, Tab. 5, Ref. 37). Full Text (Free, PDF) www.bmj.sk.
Keywords: spondyloarthropathy; ankylosing spondylitis; HLA-B27; subtype; allergy